2016
DOI: 10.1097/qai.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research: Use of Symptom Screening and Sputum Microscopy Testing for Active Tuberculosis Case Detection Among HIV-Infected Patients in Real-World Clinical Practice in Uganda

Abstract: Background The uptake of intensified active TB case finding among HIV-infected patients using symptom screening is not well understood. We evaluated the rate and completeness of each interim step in the TB “diagnostic cascade” to understand real-world barriers to active TB case detection. Methods We conducted a cohort analysis of new, ART-naïve, HIV-infected patients who attended a large HIV clinic in Mbarara, Uganda (March 1, 2012 – September 30, 2013). We used medical records to extract the date of complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…This is very low compared to the desired target of 100% and given the high burden of TB/HIV in Ghana. It is possible that this low investigation rates contributes to the high annual mortality due to TB in PLHIV [9]. Low sputum ordering in PLHIV with a positive TB screen test has been reported in a number of studies.…”
Section: Lack Of Integration Of Tb Services Into Hiv Care and Treatment Servicesmentioning
confidence: 98%
See 2 more Smart Citations
“…This is very low compared to the desired target of 100% and given the high burden of TB/HIV in Ghana. It is possible that this low investigation rates contributes to the high annual mortality due to TB in PLHIV [9]. Low sputum ordering in PLHIV with a positive TB screen test has been reported in a number of studies.…”
Section: Lack Of Integration Of Tb Services Into Hiv Care and Treatment Servicesmentioning
confidence: 98%
“…In Uganda, patients with WHO stage III or IV (indicator of more advanced disease) were more likely to have sputum order [14]. Men were more likely than women to be investigated by sputum [12,19]. It should be noted that those studies reported that men were more likely to have advanced disease (lower CD4 cells/µl) compared to women.…”
Section: Lack Of Integration Of Tb Services Into Hiv Care and Treatment Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, data from adult TB (DR and MDR) cascades in India [52] and South Africa [53] revealed major gaps along multiple steps, including diagnosis, treatment initiation, and treatment/post-treatment follow up, all needing additional attention. Data examining the TB diagnostic cascade in HIV-positive adults in Uganda demonstrated a huge drop off between the positive TB screens and obtaining sputum for testing [54]. These early studies highlight major gaps in the adult TB care cascades and allow for targeted areas of improvement.…”
Section: Introductionmentioning
confidence: 95%
“…Whereas this recommendation was made for TB screening among PLHIV, only a small proportion of PLHIV with a positive TB symptom screen test are referred for sputum examination for TB detection, even in high-burden TB/HIV settings [13]. For example, only 13.2%, 8%, and 37.1% of HIV-infected patients with a positive TB screen test had a sputum order documented for gene expert examination or chest x-ray for further active TB detection in Uganda, Kenya and Tanzania, respectively [14][15][16]. In addition, only 54.9% of HIVinfected patients with a positive TB symptom screen test were referred for sputum smear examination in Uganda [14].…”
Section: Introductionmentioning
confidence: 99%